Exploring self-perception of community pharmacists of their professional identity, capabilities, and role expansion - Anas Mustafa Salim; Bashir Elgizoli (Wolters Kluwer Medknow Publications, 2016)
Objective: The principal aim of this study was to explore the self-perception of community pharmacists of their professional identity and roles and how they think patients and doctors perceive them. The study also aimed at exploring their opinions regarding role expansion and how they assess their capabilities. Methods: This is an exploratory study that employed qualitative method. Individual, in-depth interviews were conducted with a purposive sample of 50 community pharmacists working in Khartoum State, Sudan, from October to November 2015. Each interview was recorded, transcribed, and coded into themes. Thematic analysis was carried out. Findings: The study revealed nine different identities of community pharmacists including supplier of medicines, medicines maker, dispenser, patient counselor, medicines expert, clinical practitioner, health promoter, monitor of medicines use, and family practice identity. Participants described that most of the patients value their professional role while doctors perceive them as merely dispensers. Most of participants believe that they are capable to fulfill their roles; however, they identified the need for continuous education. The study revealed that community pharmacists are thirst to role expansion. Conclusion: The study concluded that community pharmacists are aware of the different identities of their profession. The good recognition of their role by patients reflects good service provided while lack of integrated primary health care system that join doctors and pharmacists resulted in lack of pharmacists' recognition by doctors. Continuous educational program is needed for community pharmacists, and role expansion will allow for better self-perception and better profession contribution in healthcare.